Justice - Orna Sánchez, Oswaldo (2011)
Justice is the main value, which the law tries to achieve through its different expressions. The meaning of justice changes through time, social changes and geographical areas. For some philosophers, justice was one of the notes of divinity; for others, a universal virtue; and for some, science or wisdom, harmony, etc. Thus, for Plato, justice is a characteristic of the city and of each man; for Aristotle, a perfect virtue; for Saint Augustine, love; for Santo Tomás, a fundamental mode of regulation of human relations. Also, many philosophers have developed different theories about justice. The objective of this article is to internalize in the diligent reader moral values ​​for the resurgence of our society in this millennium of great social injustice.